Tensor-based framework with model order selection, denoising and high accuracy matrix decomposition for third generation global positioning system time-delay estimation in dynamic multipath scenarios - Zanatta, Mateus da Rosa (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.